Solar light trap as a new approaches for the management of bagworm, (Family:Psychidae) in oil palm plantation / Mohamad Amirul Abdul Halim - Abdul Halim, Mohamad Amirul (Faculty of Plantation and Agrotechnology, 2017)
The environmental friendly concept was adopted by oil palm industry in Malaysia has been totally change the approaches of pest management programs. It is important to provide the healthy oil palm as a step to get high profitability. However, the oil palm industry nowadays faced the pests and disease. The light trap technique is the better integrated pest management in order to not over dependent on the chemical pesticide. This research was to identify whether the light source can be applied in order to control the nocturnal pest population in oil palm, the effectiveness of light source can attract the nocturnal pest towards it and as an alternative to control measure without over dependent on the chemical usage. This study was conducted in oil palm plantation in Felcra Nasaruddin, Bota, Perak and obtained 404 individual of insects which are divided into five types. The number of the insect collected are analysed using two-way ANOVA, correlation and regression (Pearson correlation of 1 and 6 = 0.404 and P-Value = 0.027). Meanwhile, the attractiveness of the nocturnal pest is based on the level of brightness of light source. The different age of oil palm tree was considering as the main factors that were effect the population of bagworm.